Multidisciplinary Telemedicine in Healthcare During and After the COVID-19 Pandemic: A Narrative Review - Angelica Gherman; Diana Andrei; Călin Marius Popoiu; Emil Robert Stoicescu; Mihaela Codrina Levai; Isabella Ionela Stoian; Vlad Bloancă (Life)
The COVID-19 pandemic accelerated the adoption of virtual multidisciplinary teams (MDTs), transforming healthcare delivery through telemedicine. This review examines the integration of telemedicine into multidisciplinary care across various medical specialties, highlighting its benefits and challenges. A comprehensive literature search was conducted across PubMed, Google Scholar, Scopus, and Web of Science, using keywords related to telemedicine and MDTs. Inclusion criteria focused on studies discussing telemedicine implementation in multidisciplinary care, as well as its effectiveness and impact on patient outcomes, while non-English studies, single-case reports, and articles lacking explicit discussions on MDT integration were excluded. Data extraction covered telemedicine platforms, specialties involved, patient satisfaction, and clinical outcomes. Our findings suggest that virtual MDTs enhance efficiency, accessibility, and patient satisfaction, particularly in remote and underserved areas. However, challenges, such as technological barriers, disparities in digital access, and maintaining effective team communication, persist. Despite these limitations, telemedicine has demonstrated significant potential in improving diagnostic accuracy and treatment coordination. Future efforts should focus on optimizing infrastructure, digital training for healthcare providers, and regulatory frameworks to guarantee long-term sustainability.